THE POWER OF PROOF OF ELECTRONIC GROUND CERTIFICATES IN GROUND DISPUTES - Resha Biantiputri (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2023)
Ground is a basic human need, that cannot be separated. Indonesia is currently undergoing a period of digital transformation, wherein traditional analog processes are being replaced by digital alternatives through the utilization of advanced technologies. Digital transformation encompasses the utilization of advanced technologies, including machine learning, big data, and the Internet of Things, to revolutionize business operations. The research methodology employed by researchers in formulating this legislation is characterized by descriptive analysis. This approach entails the comprehensive presentation and elucidation of data to facilitate a thorough discussion. Subsequently, the data undergoes analysis through the lens of legal theories, statutory regulations, and the perspectives of researchers. From a legal standpoint, an electronic certificate is deemed legally binding due to its status as electronic evidence, as articulated in Article 5, paragraph (1) of the Electronic Information and Transactions Law. There are two methods of substantiating this claim, namely by presenting electronic documents within the electronic system before a judge, and by accessing said documents through electronic devices. The certificate functions as a formal document that provides substantial evidence of the rights associated with the physical and legal information documented in the measurement letter and ground book under consideration. The recognition of electronic evidence plays a crucial role in ensuring protection and legal certainty for all parties involved in both criminal and civil cases.